+0  
 
0
348
1
avatar+164 

Let p, q, and r be constants. One solution to the equation (x-p)(x-q) = (r-p)(r-q) is x=r. Find the other solution in terms of p, q, and r.

 Mar 26, 2018
 #1
avatar+95985 
+2

Expand and we have that

 

x^2 - (p + q)x + pq  = r^2 - (p+ q)r  + pq

 

x^2  - (p + q)k - r^2 + (p + q)r   = 0

 

The sum of the roots  =  (p + q) / 1   = p + q

The product of the roots  is [ -r^2  + (p + q)r] / 1  =  -r^2  + (p + q)r

 

Since  r  is one solution

 

Let  s   be the other   and we have

 

So

 

r + s  = p + q

s  = p + q  - r

 

Verify  that

 

r * s  =    r ( p + q - r)   =  -r^2  + (p + q)r

 

 

cool cool cool

 Mar 26, 2018

40 Online Users

avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.